2020
DOI: 10.1080/13696998.2020.1718156
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of atezolizumab versus docetaxel and nivolumab in the treatment of non-small cell lung cancer as a second line in France

Abstract: Aim: To estimate the cost-effectiveness of atezolizumab compared with docetaxel and nivolumab for the treatment of advanced non-small cell lung cancer (NSCLC), as a second-line treatment, in a French setting. Materials and methods: A three-state partitioned-survival model was developed (progression-free survival, post-progression survival, death) based on the phase IIIOAK trial on a 10-year time horizon. The comparison between nivolumab and atezolizumab came from a network meta-analysis. Utilities were estimat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
1
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 20 publications
2
1
0
1
Order By: Relevance
“…To date, several cost-effectiveness analyses of atezolizumab have been published, most focused on lung and breast cancers, from the payers' perspective in the USA, China, France and Canada. [28][29][30][31] The majority of findings were similar to ours, indicating that although immunotherapy appeared to be promising in terms of effectiveness in clinical practice, it is still an expensive alternative to the current standard of care. Therefore, a reduction in price is warranted to make the combination of atezolizumab and bevacizumab costeffective and affordable.…”
Section: Discussionsupporting
confidence: 84%
“…To date, several cost-effectiveness analyses of atezolizumab have been published, most focused on lung and breast cancers, from the payers' perspective in the USA, China, France and Canada. [28][29][30][31] The majority of findings were similar to ours, indicating that although immunotherapy appeared to be promising in terms of effectiveness in clinical practice, it is still an expensive alternative to the current standard of care. Therefore, a reduction in price is warranted to make the combination of atezolizumab and bevacizumab costeffective and affordable.…”
Section: Discussionsupporting
confidence: 84%
“…Among the three immune checkpoint inhibitors currently approved for treating advanced NSCLC, atezolizumab is the therapy associated with lower healthcare costs in the Lombardy setting. This data is consistent with a French cost-effectiveness study that concluded that atezolizumab is a cost-saving alternative to nivolumab, based on list price [15]. The cost-effectiveness of atezolizumab versus nivolumab for second-line treatment was also evaluated in a recent Canadian study based on RCT data, in which atezolizumab was more effective and less costly than nivolumab, although based on a modest difference in quality-adjusted life years (QALYs) and costs [16].…”
Section: Discussionsupporting
confidence: 79%
“…59 Their results indicated that atezolizumab was more efficacious and more costly than docetaxel in treating advanced NSCLC. 86 All studies that have assessed PD-1/PD-L1 inhibitors as secondline therapies are summarised in Table 3.…”
Section: Pd-1/pd-l1 Inhibitors As Second-line Treatment In Advanced N...mentioning
confidence: 99%